Influence the development of explosive power and speed of the arms deals - Samoum, Ali (Journal of Physical Education, 2007)
Basketball is characterized as one of the games that require its players to perform skills of specific characteristics and a precise technique. The performance of these skills is linked to specific requirements, the most important of which is power, this is clearly exemplified in the skill of shooting from jump shoot because this type of shooting requires the ability to jump to reach the highest level and the capability of the arm to push the ball strongly and speedily till it precisely reaches the net. The feature of the powers characterized by speed and explosiveness is linked to the performance of shooting from jumping more than in the other forms of power. These two powers can be developed by doing exercises, jacket exercises and medical balls and playometric exercises and others. The significance of this research lies in developing the power that is characterized by explosiveness and speed through the exercises of power, and identifying the effect of this develop on the level of jump shoot for basketball players. Aims of the research: • Knowing the effect of power exercises on the development of the power characterized by explosiveness and speed of arms and feet for advanced level basketball players. • Knowing the effect of power exercises on the development of the power characterized by explosiveness and speed of arms and feet on the level of jump shoot for advance level basketball players. Hypotheses of the research:- • The use of power exercises has a positive effect on the development of power characterized by explosiveness and speed of arms and feet for advance level basketball players. • The development of power characterized by explosiveness and speed of arms and feet for advance level basketball players has a positive effect on the improvement of the level of jump shoot. After presenting, analyzing and discussing the results the researcher concludes the following:- 1. Power exercises have a positive effect on the powers characterized by explosiveness and speed of arms and feet. 2. The development of the powers characterized by explosiveness and speed of arms and feet has an effect on the development of the level of jump shoot. 3. The results showed that the experimental group that used power exercises surpassed the disciplined group in all the variables of the study. The researcher recommends:- 1. It is necessary to vary the techniques of skill training during training units, like the skill of jump shoot in basketball. 2. The use of the variable power exercises as a training technique develops the performance of jump shoot. 3. inventing similar training techniques can develop the physical and skills aspect simultaneously and to be performed inside the ground for economy of effort, time and money exerted